Strategic Approach in Reaching Generation Z in Tangerang: A Case Study of Fore Coffee - Kusuma, Rusbiansyah Perdana; Khairunnisyah, Adinda Rizky; Fitriah, Dhita Dhiya’ul (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2024)
This study aims to explore marketing strategies that are effective in reaching and influencing the purchasing behaviour of Generation Z in Tangerang City towards coffee products, with a focus on Fore Coffee. The SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method with IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) approaches were used to evaluate the internal and external factors affecting the company in this market. Data was collected through online surveys with respondents who are members of Generation Z in Tangerang City. The results of this study provide deep insights into the preferences and purchasing tendencies of the younger generation towards coffee products, with strategic implications for future marketing and product development.